The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1097/01.ccm.0000060014.75282.69
|View full text |Cite
|
Sign up to set email alerts
|

Arginine vasopressin, but not epinephrine, improves survival in uncontrolled hemorrhagic shock after liver trauma in pigs*

Abstract: Vasopressin, but not epinephrine or saline placebo, improved short-term survival in a porcine model of uncontrolled hemorrhagic shock after liver injury when surgical intervention and fluid replacement was delayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(70 citation statements)
references
References 26 publications
3
60
1
3
Order By: Relevance
“…We have shown beneficial effects of vasopressin vs. epinephrine in porcine models with hemorrhagic shock (33)(34)(35). In the clinical setting, we observed positive effects of vasopressin in some patients with life-threatening hemorrhagic shock with collapsing arterial blood pressure who did not respond anymore to adrenergic catecholamines and fluid resuscitation.…”
Section: The Futurementioning
confidence: 73%
“…We have shown beneficial effects of vasopressin vs. epinephrine in porcine models with hemorrhagic shock (33)(34)(35). In the clinical setting, we observed positive effects of vasopressin in some patients with life-threatening hemorrhagic shock with collapsing arterial blood pressure who did not respond anymore to adrenergic catecholamines and fluid resuscitation.…”
Section: The Futurementioning
confidence: 73%
“…Recent studies have reported that it has beneficial effects on endotoxic [2], hemorrhagic and advanced vasodilatory shock [3][4][5][6][7]. The effect of AVP improving cardiovascular function during shock is thought to be mediated through the V1a receptor and by increasing the intracellular Ca 2+ via mobilization of intracellular stores and entry of extracellular Ca 2+ via specific calcium channels.…”
Section: Introductionmentioning
confidence: 99%
“…Arginine vasopressin has been studied in a swine model of penetrating liver injury that involved approximately 40 % loss of estimated blood volume [28]. The animal was treated with vasopressin and had higher blood pressures, and lower hemorrhage volume, when compared to animals treated with either epinephrine or saline.…”
Section: Adjuncts For Hemostasismentioning
confidence: 99%